2022
DOI: 10.1021/acsnano.1c10709
|View full text |Cite
|
Sign up to set email alerts
|

Systemically Administered TLR7/8 Agonist and Antigen-Conjugated Nanogels Govern Immune Responses against Tumors

Abstract: The generation of specific humoral and cellular immune responses plays a pivotal role in the development of effective vaccines against tumors. Especially the presence of antigen-specific, cytotoxic T cells influences the outcome of therapeutic cancer vaccinations. Different strategies, ranging from delivering antigen-encoding mRNAs to peptides or full antigens, are accessible but often suffer from insufficient immunogenicity and require immune-boosting adjuvants as well as carrier platforms to ensure stability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 66 publications
0
34
0
2
Order By: Relevance
“…To explore this notion, TLR agonists, CpG, and imidazoquinoline derivatives were selected for our studies because they have a venerable history as vaccine adjuvants. , CpGs are synthetic oligodeoxynucleotides that trigger toll-like receptor 9 and activate innate immune responses by producing Th1-associated cytokines. , Although imidazoquinoline derivatives were identified as TLR 7/8 agonists, they induce pro-inflammatory cytokines such as TNF alpha and IL-12 . Both CpGs and imidazoquinoline have been extensively used as adjuvants in several vaccines. However, to the best of our knowledge, they have never been studied together on a nanotechnology platform.…”
Section: Resultsmentioning
confidence: 99%
“…To explore this notion, TLR agonists, CpG, and imidazoquinoline derivatives were selected for our studies because they have a venerable history as vaccine adjuvants. , CpGs are synthetic oligodeoxynucleotides that trigger toll-like receptor 9 and activate innate immune responses by producing Th1-associated cytokines. , Although imidazoquinoline derivatives were identified as TLR 7/8 agonists, they induce pro-inflammatory cytokines such as TNF alpha and IL-12 . Both CpGs and imidazoquinoline have been extensively used as adjuvants in several vaccines. However, to the best of our knowledge, they have never been studied together on a nanotechnology platform.…”
Section: Resultsmentioning
confidence: 99%
“…More recently in 2022, the same group also developed a pH-responsive nanogel platform, using OVA and TLR7/8 agonists, which could be modularly modified into nanogels, resulting in two-component nanogels that effectively inhibited tumour growth in both preventive and therapeutic assays and thus, provided the opportunity to establish cancer-specific immunity. 257 It was found that the expression of CD80 and CD86 of DCs in the spleen was enhanced, and induced the activation of downstream T lymphocytes. This nanogel could effectively prevent systemic inflammation due to massive systemic immune activations compared to the off-target effects of small-molecular IMDQ (Fig.…”
Section: Nanogels For Immunomodulatory Therapeuticsmentioning
confidence: 99%
“…In previous reports, we could demonstrate that various types of macromolecular carriers can spatiotemporally control the delivery of covalently attached IMDQ while omitting the drug's systemic inflammatory offtarget effects. [22,26,[85][86][87][88][89] Giving the fact that the empty nanogel NP(-) remained immunologically silent during the in vitro experiments, we therefore administered the IMDQ-nanogel NP(IMDQ) versus the soluble drug sIMDQ subcutaneously into the footpad of mice. We aimed for a focused delivery of the nanogels to the draining lymph nodes followed by a local activation of lymph node residing and infiltrating immune cells while excluding a systemic activation of immune system.…”
Section: In Vivo Performance Of Immunostimulatory Nanogels For Lymph ...mentioning
confidence: 99%